Pigment Epithelium-Derived Factor Promotes the Growth and Migration of Human Esophageal Squamous Cell Carcinoma - Tang, De-Rong; Li, Cheng-Lin; Xu, Ke-Ping; Wu, Qing-Quan; Chen, Qi-You; Lv, Jun-Jie; Ji, Jian; Zang, Bao; Chen, Chen; Gu, Biao; Zhao, Jian-Qiang (Frontiers in Oncology, 2020)
Pigment epithelium-derived factor (PEDF) is known as an oncogene in various types of cancers. However, how PEDF affects the development of human esophageal squamous cell carcinoma (ESCC) is unknown. This study investigates the role of PEDF in ESCC cell proliferation, migration, and cell cycle both in vitro and in vivo. The PEDF expression was examined in patient tumour samples and ESCC cell lines. Short hairpin RNA technology was used to inhibit the PEDF expression in the cell ESCC lines EC9706 and KYSE150 by. In vitro cell proliferation and migration assays were performed. The effects of PEDF on tumour growth, progression, migration, and tumour cell apoptosis were examined in vivo in murine subcutaneous xenograft tumour models. It was found that PEDF was overexpressed in esophageal cancer cells and patient tumour tissues compared to normal control samples. Knock down of PEDF inhibited esophageal cell proliferation and migration in vitro. Moreover, inhibition of PEDF expression in human ESCC cells significantly reduced tumorigenesis in vivo. PEDF enhanced cell cycle progression and inhibited cell apoptosis. Inhibition of PEDF significantly reduced tumour growth and tumour size in vivo. These results indicate that PEDF induce tumorigenesis in ESCC and can be a potential therapeutic target for cancer treatment.